Downregulation of the expression of bone morphogenetic protein 7 in experimental pyelonephritis - ALPAY, HARİKA; İLKİ, ZEYNEP ARZU (SPRINGER, 2005)
Bone morphogenetic protein 7 (BMP 7) is a member of the transforming growth factor (TGF) beta superfamily and is involved in regeneration, repair, and development of specific tissues, for example kidney, gut, lens, and skeleton. BMP 7 has emerged as a renotrophic factor and experimental studies have shown its protective role against fibrotic processes. Tubulointerstitial changes are present in the pyelonephritic kidney which progresses to fibrosis. Renal fibrosis may lead to significant morbidity in the form of hypertension, proteinuria, and loss of renal function. The objective of this study was to investigate BMP 7 expression in experimental acute and chronic pyelonephritis models. Eighteen Wistar rats were injected with 0.1 mL solution containing E. coli ATCC 25922 10(10) cfu mL(-1) into left renal medullae. Six rats were used as a sham group and were given 0.1 mL 0.9% NaCl. Pyelonephritic rats were sacrificed 24 h (group I, n=6), 1 week (group II, n=6), and 6 weeks (group III, n=6) after E. coli injection. Serum creatinine levels were analyzed. Renal tissues were studied histopathologically by use of hematoxylin and eosin and scored for diagnosis of pyelonephritis. BMP 7 expression was studied semiquantitatively by immunohistochemical staining. Acute (group I) and chronic (group II and group III) pyelonephritic histopathological changes were observed in experimental pyelonephritic groups. A gradual decrease in BMP 7 expression was observed in the tubulointerstitial and tubular area of the pyelonephritic kidneys, mildest in the acute pyelonephritic group and most severe in the chronic pyelonephritic 6th week group. A statistically significant difference was observed between tubulointerstitial BMP 7 expression by groups I and III (P=0.017) and by groups III and IV (P=0.000). Tubular BMP 7 expression was statistically significantly different between groups II and IV (P=0.009) and between groups III and IV (P=0.002). The data imply that BMP 7 has a major role in chronic pyelonephritis. Tubulointerstitial and tubular BMP 7 expression also had a significant negative correlation with fibrosis, tubular, atrophy, and vascular changes. Serum creatinine levels of the study group were all normal. We conclude that the decrease in renal BMP 7 expression in experimental chronic pyelonephritis is one of the factors responsible for fibrotic changes in persistent renal damage.
Keywords: bone morphogenetic protein (BMP 7); acute pyelonephritis; chronic pyelonephritis; experimental; fibrosis; GROWTH-FACTOR-BETA; ASCENDING PYELONEPHRITIS; RENAL FIBROSIS; ANGIOTENSIN-II; BMP-7; KIDNEY; INDUCTION; FAILURE; REFLUX